Hemispheric asymmetries and emotions: Evidence from effective connectivity. (December 2018) - Wyczesany, Miroslaw; Capotosto, Paolo; Zappasodi, Filippo; Prete, Giulia
Abstract: The Right Hemisphere Hypothesis (RHH) posits that the right hemisphere is specialized in processing all emotions; the Valence Hypothesis (VH) suggests a left/right-hemispheric specialization for positive/negative emotions, respectively. Behavioural, neuroimaging and physiological investigations alternatively support either the RHH or the VH, but connectivity analyses have been hardly exploited in this field. In the present study, unilateral and bilateral presentations of positive (happy) and negative (angry) emotional faces were used during electroencephalographic (EEG) recordings, and estimation of effective connectivity was performed using the Directed Transfer Function, to estimate causal influences between brain regions (Granger causality approach). The results show a strong pattern of connectivity among different frontal areas (orbitofrontal and dorsolateral prefrontal cortex), attentional network (frontal eye field, intraparietal sulcus), visual occipital areas and temporal sites, mainly lateralized in the right hemisphere for all emotions, in accordance with the RHH. Moreover, a stronger pattern of connectivity is evident when stimuli are presented in accordance with the VH (positive/negative emotions to the left/right hemisphere, respectively). Finally, the results suggest a crucial role of the right dorsolateral prefrontal cortex in a top-down regulation toward different areas involved in emotional processing. We conclude that the RHH and the VH are not mutually exclusive, but they seem to coexist during affective perception. Highlights: Hemispheric lateralization theories were tested using hybrid faces paradigms. Effective connectivity was used to check cortical communication patterns. Perceptual, attentional and executive regions were assessed. Right hemisphere theory and the valence theory are not mutually exclusive.